Antipyretic Effectiveness Test from Dragon (Pyrosia piloselloides) (L) M. G. Price) Leaves Extract in Male Marmutes (Cavia Procellus) - Edi Kamal, Sainal; Prayitno, Suprapto; Hamdi, Syaibatul (Jurnal Farmasi Sandi Karsa, 2021)
This study aims to determine Effectiveness Of Dragon Scale Leaves (Pyrrosia piloselloides (L.) M. G. Price) As An Antipyretic In Male Marmut (Cavia porcellus) induced with 5% peptone. This study used 15 male guinea pigs which were divided into V groups. roup I was given negative control (Na. CMC 1% w/v), groups II, III and IV were given dragon scales leaf extract at a dose of 250 mg/kg, 500 mg/kg, and 750 mg/kg and group V was given a positive control. (Paracetamol). previously induced with 5% peptone subcutan. measurements of body temperature rectally were carried out every 30 minutes, survived 4 hours. The results showed that the administration of dragon scales leaf extract at a dose of 250 mg/kg, 500 mg/kg, and 750 mg/kg of body weight gave an antipyretic effect against male guinea pigs and the most optimal effect is obtained at a dose of 750 mg/kgBW which is 129,05% compared to paracetamol which is 146,19%.